A prospective study of psychological distress after prostate cancer surgery. Issue 12 (10th November 2019) - Occhipinti, Stefano; Zajdlewicz, Leah; Coughlin, Geoffrey D.; Yaxley, John W.; Dunglison, Nigel; Gardiner, Robert A.; Chambers, Suzanne K.
Abstract: Background: Men treated for prostate cancer experience heightened psychological distress and have an increased risk of suicide. Management of this distress and risk is crucial for quality urological care. Objective: To identify risk indicators for poorer trajectories of psychological adjustment and health‐related quality of life (QoL) after surgery for localised prostate cancer. Design, Setting, and Participants: Patients were newly diagnosed with localised prostate cancer scheduled for surgical treatment. Patients were assessed at baseline (pre‐surgery) and 6 weeks, 3 months, 6 months, 12 months, and 24 months post–surgery. Measurements: Assessment measures included sociodemographics, domain‐specific and health‐related QoL, and psychological distress. Mixed effects regression models were used to analyse the data. Results and Limitations: A total of 233 patients provided data for this analysis (Mage = 60 years, standard deviation [SD] = 4.02; MPSA = 7.37 ng/mL). At baseline, the prevalence of high psychological distress was 28% reducing to 21% at 24 months. Before treatment, younger age, more comorbidities, and worse bowel function were related to greater psychological distress; and younger age and better urinary, sexual, and bowel function were related to better health‐related QoL. By contrast, for changes over time, only bowel function was important with better bowel function predicting decreasing psychological distress for men. Conclusions: Regular distress screening is indicated over the 24 months after surgery for localised prostate cancer. Care pathways for men with prostate cancer need also to respond to age‐specific concerns and health problems associated with comorbidities in aging men. Focussed symptom control for bowel bother should be a priority.